“Would you ever say that to me in class?”: Exploring the Implications of Disinhibition for Relationality in Online Teaching and Learning - Rose, Ellen (Proceedings of the International Conference on Networked Learning, 2014)
Despite years of study and theorizing, we know very little about students’ and instructors’ experiences of relationality in online courses. This paper reports on a two-university qualitative study that sought insight into the nature and experience of relationality in asynchronous, text-based courses in which teacher and students do not come face to face. Interviews with 20 instructors and 20 students from a variety of disciplines revealed that their experiences of connection with, or disconnection from, each other were profoundly influenced by the phenomenon of online disinhibition. The online disinhibition effect is defined as the tendency of people to behave in unrestrained ways when interacting with others online. These behaviours have been classified as “benign” or “toxic.” Disinhibition has long been identified and recognized by psychologists as a factor in computer-mediated communications, but there is little research illuminating the role it plays in online teaching and learning, and what there is tends to be inconclusive. While several studies show that students do tend to behave in unrestrained ways when interacting online, students in the online course studied by Conrad (2002a and 2002b) demonstrated increased inhibition. Both students and instructors in the current study reported on many instances of benign and toxic disinhibition, although stories about the latter were more prevalent. Benign disinhibition was manifested in stories of shy students who participated more freely online, and in stories of students who disclosed more about themselves than they would face-to-face. Toxic disinhibition was manifested in stories about angry and abusive emails and posts. Students also indicated that their awareness of the possibility of anger erupting easily through miscommunication resulted in an “excessive niceness.” Thus inhibition may be a paradoxical response to the increased possibility of disinhibited behaviour in online learning environments. This study found that disinhibited behaviour, whether in its benign or toxic form, is a factor that powerfully affects the nature of student-student and student-teacher relationships in online courses.